Efecto in vitro de extractos etanólicos de mangifera indica, Tamarindus inidca y Cassia angustifolia sobre el crecimiento de Salmonella typhi y Escherichia coli ATCC 25922. - Untol Paredes, Edit Roxana (2018)
ABSTRACT The aim of the present investigation was to evaluate the in vitro effect of ethanolic extracts of Mangifera indica, Tamarindus indica and Cassia angustifolia on the growth of Salmonella typhi and Escherichia coli using a completely randomized factorial design. To obtain the ethanolic extracts of leaves of M. indica "mango", T. indica "tamarind" and C. angustifolia "senna leaf" were placed 30 g. of powder of the leaves to distillation in soxlet equipment with 200 ml of 95% ethanol, the obtained distillate was dried with air and all the obtained was mixed in 100 ml of PBS (phosphate buffered saline), obtaining a mother solution, dilutions of the obtained extracts were made at two concentrations (50% and 25%) in PBS, then 1.5 ml of each extract was taken at 50% and mixed, in the same way we proceeded with the obtained extracts at 25% to obtain a mixture at 50% and 25% respectively. The inoculum of S. typhi and E. coli was prepared with a turbidity level of tube N° 0.5 on the Mc Farland scale (1x108) and plated with Muller Hinton agar to evaluate the effect of the extracts for it used the method originally described by Kirby-Bauer with 0.7 mm diameter Watman paper discs No 4, which were immersed in each of the prepared extracts, dried in an oven at 30 °C, then placed in an oven discs per plate (four extracts prepared including the mixture and a positive control (ciprofloxacin drug disk), for the two bacterial strains, the inoculated plates were incubated at 37ºC for 24 hours to then measure the diameters of the zone of inhibition. show the significant differences between the effects of the extracts having greater effect the ethanolic extract of M. indica "mango" with an inhibition halo of 16.5 mm on S. typhi and of 15.2 for E. coli at at 50% concentration and this probably would be due to the mangiferin a polyphenol contained in the ethanolic extract of M. indica would produce the inhibition of the bacterial growth in the cultures.